The Relationship Between Students’ Perceptions of Guidance and Counseling Teachers and Their Interest in Counseling - Imam Wahyu Wijaya; Wiffy zalina Putri (Journal of Psychology and Education Counseling (JPEC), 2025)
This study aims to examine the relationship between students’ perceptions of guidance and counseling (GC) teachers and their interest in participating in counseling services. The research employed a quantitative approach with a correlational design. The population consisted of 1,148 students of SMA Negeri 2 Kendal, from which 260 students were selected as the research sample. The research instrument was developed through several stages: constructing the instrument blueprint, designing the items, conducting a try-out, and revising invalid items. Data were analyzed using descriptive statistics and Pearson’s product–moment correlation. The descriptive results indicate that students’ counseling interest is categorized as high (M = 63.7; SD = 8.73), as is their perception of GC teachers (M = 74.7; SD = 9.68). The correlation analysis shows a strong and significant relationship between students’ perceptions of GC teachers and their counseling interest (r = 0.771; p < 0.05). These findings suggest that the more positive students’ perceptions are of their GC teachers, the higher their interest in engaging in counseling services.